Characterisation of the cold-shock response in Mycobacterium smegmatis - Shires, Karen Lesley (Division of Medical Microbiology, 2017)
The response of Mycobacterium smegmatis to a cold shock was investigated in order to gain insight into the stress responses of members of the genus Mycobacterium. Mycobacterium smegmatis cultures were shocked from 37°C to 30°C, 25°C, 15°C, and 10°C and the effects on both growth (ATP concentration, culture turbidity, colony-forming units) and metabolism (incorporation of ¹⁴C-leucine and ³H-uracil) were investigated. The magnitude of the cold-shock response was found to be dependent upon the degree of the cold shock. A cold shock to 10°C had the greatest effect and resulted in a "lag period" of 24 hours in both the growth and metabolism of the culture. The synthesis of proteins was reduced 20-fold during this period, indicating at block in translation. The cold-shock response in Mycobacterium smegmatis was an adaptive response with growth eventually being resumed at the colder temperature, but at a reduced rate. Using the techniques of one-dimensional sodium-dodecyl-sulphate polyacrylamide gel electrophoresis and two-dimensional protein gel electrophoresis, ³⁵S-methiononine-labelled proteins that were synthesised during the cold shock were analysed. At least fourteen radio-labelled proteins were induced during the first 24-hour period and these demonstrated two distinct patterns of cold-shock induced expression: transient and continuous. Depending upon the pattern of expression and size, the cold-shock proteins were classified as "cold-induced proteins", "cold-shock proteins" or "cold-acclimation proteins". CipM, a 27kDa protein, was identified as the major cold-shock protein through one-dimensional protein electrophoresis. From N-terminal sequence data generated from a protein (CipM.1) within this band, a corresponding degenerate DNA probe was used to isolate cipM.1. This gene was cold-inducible, with mRNA levels transiently increasing 5-7 fold after a 37°C to 10°c cold-shock. Homologues of this cold-shock gene are found in the genomes of Mycobacterium tuberculosis and Mycobacterium leprae. The corresponding mycobacterial proteins showed homology at the N-terminus to the HU~ subunit of HU of Escherichia coli and possessed similar C-terminal praline, lysine and alanine degenerate repeats to the mycobacterial heparin-binding hemagglutinin. The response of several mycobacterial cold-shock gene homologues to a cold shock was also investigated, by northern-hybridisation and S1 nuclease analysis. The cspA homologue of Mycobacterium smegmatis demonstrated a 16-24 fold transient induction in mRNA levels following a 37°C to 10°C temperature-shift, while gyrA mRNA levels were maintained at a constant level throughout the cold shock. Although some similarities were demonstrated between the cold-shock response of Escherichia coli and Mycobacterium smegmatis, definite differences occur in the proteins that are involved in the adaptive stages of the response.